2023
DOI: 10.48550/arxiv.2302.01880
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Towards Inclusive Avatars: Disability Representation in Avatar Platforms

Kelly Mack,
Rai Ching Ling Hsu,
Andrés Monroy-Hernández
et al.

Abstract: Digital avatars are an important part of identity representation, but there is little work on understanding how to represent disability. We interviewed 18 people with disabilities and related identities about their experiences and preferences in representing their identities with avatars. Participants generally preferred to represent their disability identity if the context felt safe and platforms supported their expression, as it was important for feeling authentically represented. They also utilized avatars … Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 44 publications
0
1
0
Order By: Relevance
“…Learners may difer in age, gender, ethnicity, background, but also in cognitive and physical characteristics. From a representation standpoint, these diferences already impact avatar design [32]. From an embodiment standpoint, further considerations should be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…Learners may difer in age, gender, ethnicity, background, but also in cognitive and physical characteristics. From a representation standpoint, these diferences already impact avatar design [32]. From an embodiment standpoint, further considerations should be acknowledged.…”
Section: Discussionmentioning
confidence: 99%
“…At the beginning of our study, all participants showed an initial willingness to disclose their disabilities on avatars. Three participants (P1, P4, P5) mentioned that their disability was "an important part of my identity" (P5) and wanted their avatars to look like themselves in real life as much as possible, which confrmed the insight from prior research [45,74]. Additionally, P1 believed that avatars with DS consolidated his disability identity, "Having similar limitations [via my avatar in social VR] is really helpful for me and my comfort [...] it makes me feel more comfortable in what I need to do for myself [and] taking care of myself.…”
Section: Desire To Continue Using Avatars With Dsmentioning
confidence: 96%
“…Zhang et al [74] interviewed 19 participants who had visual and hearing impairments and revealed that PWD preferred disclosing their disabilities via avatars and adopted a spectrum of strategies to curate their images in social VR, such as revealing selective disabilities and indicating ability changes via avatars. The other work by Mack et al focused on PWD with invisible disabilities and how they managed multiple identities via avatar design [45]. They found that participants with multiple, intersecting minoritized identities needed to make trade-ofs when deciding which identities to present via avatars, especially when the expression of one identity conficted with the other (e.g., a South Asian person with albinism had difculty presenting their race and disability at the same time).…”
Section: Avatar-mediated Interaction and Identity Representation In S...mentioning
confidence: 99%
See 1 more Smart Citation